Tunable 3D nanofibrous and bio-functionalised PEDOT network explored as a conducting polymer-based biosensor - Meng, Lingyin; Turner, Anthony P. F.; Mak, Wing Cheung (Elsevier, 2020)
Conducting polymers that possess good electrochemical properties, nanostructured morphology and functionality for bioconjugation are essential to realise the concept of all-polymer-based biosensors that do not depend on traditional nanocatalysts such as carbon materials, metal, metal oxides or dyes. In this research, we demonstrated a facile approach for the simultaneous preparation of a bi-functional PEDOT interface with a tunable 3D nanofibrous network and carboxylic acid groups (i.e. Nano-PEDOT-COOH) via controlled co-polymerisation of EDOT and EDOT-COOH monomers, using tetrabutylammonium perchlorate as a soft-template. By tuning the ratio between EDOT and EDOT-COOH monomer, the nanofibrous structure and carboxylic acid functionalisation of Nano-PEDOT-COOH were varied over a fibre diameter range of 15.6 ± 3.7 to 70.0 ± 9.5 nm and a carboxylic acid group density from 0.03 to 0.18 μmol cm−2. The nanofibres assembled into a three-dimensional network with a high specific surface area, which contributed to low charge transfer resistance and high transduction activity towards the co-enzyme NADH, delivering a wide linear range of 20–960 μM and a high sensitivity of 0.224 μA μM−1 cm−2 at the Nano-PEDOT-COOH50% interface. Furthermore, the carboxylic acid groups provide an anchoring site for the stable immobilisation of an NADH-dependent dehydrogenase (i.e. lactate dehydrogenase), via EDC/S–NHS chemistry, for the fabrication of a Bio-Nano-PEDOT-based biosensor for lactate detection which had a response time of less than 10 s over the range of 0.05–1.8 mM. Our developed bio-Nano-PEDOT interface shows future potential for coupling with multi-biorecognition molecules via carboxylic acid groups for the development of a range of advanced all-polymer biosensors
Keywords: Conducting polymer; Nanofibre; Carboxylic acid functionalisation; Bio-nano-PEDOT